Kinesiology tape mediates soccer-simulated and local peroneal fatigue in soccer players - Farquharson, C.; Greig, M. (Research in Sports Medicine, 2017)
To investigate the efficacy of kinesiology taping in mediating the influence of fatigue on ankle sprain risk, 12 male soccer players completed single-leg dynamic balance trials pre- and post-exercise (soccer-specific protocol, isokinetic ankle inversion/eversion protocol) in each of three counter-balanced taping conditions (no tape, zinc oxide tape ZO, kinesiology tape KT). Balance was quantified as the overall stability index (OSI) and directional stability indices of platform deflection. Soccer-specific fatigue only increased OSI in the no tape condition (p = 0.03), with ZO and KT trials negating a fatigue affect. Localized fatigue increased OSI in the no tape (p = 0.01) and ZO (p = 0.05) trials, with no increase in the KT trial. A similar pattern was observed in medio-lateral and anterio-posterior balance indices. KT mediates soccer-simulated and local peroneal fatigue, with practical implications for epidemiological observations of increased injury risk during the latter stages of match play.